PTH-099 Probing The EGFR (Epidermal Growth Factor Receptor) Signalling Pathway in Colorectal Liver Metastases (CRLM). (17th August 2016) - Barrett, JE; Siriwardana, PN; Singh, S; Kim, P; Hochhauser, D; Davidson, BR; Ng, T
Abstract : Introduction: Overexpression and activation of the components of the EGFR/ErbB pathway has a prognostic significance in CRLM. HER2 (ErbB2) and HER3 (ErbB3) have previously been found to be overexpressed in CRLM with ErbB3 overexpression being associated with good prognosis. The ErbB signalling pathway consists of multiple molecular components. These components interact in a complex non-linear manner which makes it challenging to understand how the system functions. For example, the dimerization between ErbB receptors plays a crucial role in downstream signalling activation. Mathematical modelling can help to quantify network properties and understand its behaviour under various conditions. Birtwistle (2007) developed a mathematical model of the EGFR signalling pathway which focused on early pathway response to stimulation of the ErbB receptors. Using this model, we aimed to understand how the ErbB pathway functions in CLRM. Methods: Lysates of fresh frozen CRLM samples from 18 patients who were chemonaive for CLRM were analysed using a proteomics-based assay Collaborative Enzyme Enhanced Reactive immunoassay (CEER) to quantify the phosphorylated and non-phosphorylated forms of ErbB family receptors and phosphorylated downstream ErbB pathway factors. We used a model of the EGFR signalling pathway previously developed by Birtwistle (2007) and validated using data from a breast cancer cell line to try and reproduce the activation patterns of HER1, HER2, and HER3. Results: CRLM with high levels of both HER2 and HER3 were associated with high levels of phosphorylated HER3 (pHER3) and vice versa (p < 0.001). A similar relationship was observed between pHER3 and HER1, HER2 (p < 0.0001); and HER1, cMET (p = 0.006). Simulations focused on pHER3 for high and low levels of HER1, HER2, and HER3. The simulated relationship between pHER3 and HER1, HER2 was in good agreement with our observed data. High and low levels of both HER1, HER2 and HER1, HER3 also showed good agreement. Some discrepancy between simulation and experiment was found for high values of HER1 and low values of HER2 (and vice versa). Conclusion: Simulations were performed to understand the dynamics of the EGFR pathway and showed partial agreement between the Birtwistle model and CEER data.The Birtwistle model which was designed to only capture the early network response to stimulation of ErbB receptors in breast cancer cells may not be directly applicable to resected CRLM. Further refinement of the model is required in the future. Disclosure of Interest: None Declared